Histological Study Of Many Branches Of Aorta In Local Dog - Fatima hasab; Fawzi Al-Asadi (Kufa Journal for Veterinary Medical Sciences, 2017)
The aorta is the main artery in the body, originating from the left ventricle of the heart and extending down to the abdomen ,the study aimed  to classify the regions and the main branches of the aorta anatomically and histologically by several technique .Twenty doges (13-14 kg) weight and approximately (1.5 year) age collected from  basra market of animals ,after the anaesthesed the animals the aorta dissected and the specimen where fixed in formalin solution 10% for 48 hr or 72 hr , after that the specimen were washed in tap water until removed all formalin from the section  ,made several histological section  about  10 (mm)  and stained with H&E and special stain such as vangesion ,PAS , Mallory , wegart  stain, then the section observed under the light microscope, The result of histological study involved that all part of aorta consist of three tunics and the elastic and muscular density differ with the part of aorta